Suppression of a signal sequence mutation by an amino acid substitution in the mature portion of the maltose-binding protein. - Cover, W H (1987)
An unusual spontaneous pseudorevertant of an Escherichia coli strain carrying the signal sequence point mutation malE14-1 was characterized. The suppressor mutation, malE2261, resulted in a single substitution of an aspartyl residue for a tyrosyl residue at position 283 in the sequence of the mature maltose-binding protein. The precursor retained the malE14-1 point mutation in the signal sequence. The pseudorevertant carrying both malE14-1 and malE2261 exported twice the amount of maltose-binding protein as that of the mutant carrying the malE14-1 allele alone but only 18% of the amount exported by a strain producing wild-type maltose-binding protein. A strain carrying the suppressor allele malE2261 in combination with a wild-type signal sequence exported normal quantities of maltose-binding protein to the periplasm. Mature MalE2261 had a Kd for maltose of 27 microM, compared with 3.6 microM for mature wild-type maltose-binding protein. The precursor species than contained both changes resulting from malE14-1 and malE2261 was significantly less stable in the cytoplasm than was the precursor containing only the change encoded by malE14-1.